2018
DOI: 10.1089/ther.2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Levels and Neurologic Outcomes in Patients Undergoing Therapeutic Hypothermia After Cardiac Arrest

Abstract: Therapeutic hypothermia (TH) improves neurological outcomes after cardiac arrest by mitigating cerebral reperfusion injury. Serum magnesium (Mg) inhibits glutamate release, restores blood-brain barrier integrity, and decreases brain edema. The neuroprotective role of Mg in cardiac arrest patients undergoing TH is not well established. We analyzed 438 survivors of cardiac arrest who completed a TH protocol from 2008 through 2016. Multivariate and receiver operating characteristic (ROC) analyses examined the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Analysis of 438 survivors of cardiac arrest who completed a therapeutic hypothermia protocol, showed that lower magnesium levels at presentation and during therapeutic hypothermia were associated with favorable outcomes of cardiac arrest. Moreover, magnesium supplementation during the hospital stay was associated with improved neurological outcomes, suggesting that magnesium supplementation may potentiate the beneficial effects of therapeutic hypothermia ( 38 ). Several mechanisms explain why magnesium and hypothermia appear to act synergistically.…”
Section: Magnesium and Cardiac Arrestmentioning
confidence: 99%
“…Analysis of 438 survivors of cardiac arrest who completed a therapeutic hypothermia protocol, showed that lower magnesium levels at presentation and during therapeutic hypothermia were associated with favorable outcomes of cardiac arrest. Moreover, magnesium supplementation during the hospital stay was associated with improved neurological outcomes, suggesting that magnesium supplementation may potentiate the beneficial effects of therapeutic hypothermia ( 38 ). Several mechanisms explain why magnesium and hypothermia appear to act synergistically.…”
Section: Magnesium and Cardiac Arrestmentioning
confidence: 99%
“…8 Hypomagnesaemia has also been associated with poor neurologic outcomes in patients suffering from post-cardiac arrest syndrome (PCAS). 9 Other electrolytes are also of importance in this context. Hypocalcaemia can cause reduced cardiac contractility and decreased vascular tone, 10 while hypophosphatemia can cause muscle weakness and reduced diaphragmatic contractility, leading to difficulties weaning from a ventilator.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium plays an important role in many cellular functions, and hypomagnesemia may induce cardiac arrhythmias and interfere with vascular tone 8 . Hypomagnesaemia has also been associated with poor neurologic outcomes in patients suffering from post‐cardiac arrest syndrome (PCAS) 9 . Other electrolytes are also of importance in this context.…”
Section: Introductionmentioning
confidence: 99%